2022
DOI: 10.1007/s00126-022-01146-8
|View full text |Cite
|
Sign up to set email alerts
|

Orogenic gold: is a genetic association with magmatism realistic?

Abstract: Many workers accept a metamorphic model for orogenic gold ore formation, where a gold-bearing aqueous-carbonic fluid is an inherent product of devolatilization across the greenschist-amphibolite boundary with the majority of deposits formed within the seismogenic zone at depths of 6–12 km. Fertile oceanic rocks that source fluid and metal may be heated through varied tectonic scenarios affecting the deforming upper crust (≤ 20–25 km depth). Less commonly, oceanic cover and crust on a downgoing slab may release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 207 publications
0
15
0
Order By: Relevance
“…Considering the Jiaodong gold deposits were originally considered to be orogenic type (Goldfarb et al, 2001(Goldfarb et al, , 2007, metamorphic fluid was once regarded as a possible source. The metamorphic fluid genesis model suggests that fluids, sulfur, and gold are released respectively from progresses of chlorite converting to biotite and pyrite converting to pyrrhotite, during progressive metamorphism in the continental crust or in the subducting oceanic slab (Large et al, 2007;Phillips and Powell, 2010;Tomkins, 2010;Goldfarb and Pitcairn, 2022). The magmatic fluid suggests that the deep magmatic activity provides ore-forming fluids, material, and heat source for mineralization (Fan et al, 2003).…”
Section: Source Of Ore-forming Fluids and Metallogenic Modelmentioning
confidence: 99%
“…Considering the Jiaodong gold deposits were originally considered to be orogenic type (Goldfarb et al, 2001(Goldfarb et al, , 2007, metamorphic fluid was once regarded as a possible source. The metamorphic fluid genesis model suggests that fluids, sulfur, and gold are released respectively from progresses of chlorite converting to biotite and pyrite converting to pyrrhotite, during progressive metamorphism in the continental crust or in the subducting oceanic slab (Large et al, 2007;Phillips and Powell, 2010;Tomkins, 2010;Goldfarb and Pitcairn, 2022). The magmatic fluid suggests that the deep magmatic activity provides ore-forming fluids, material, and heat source for mineralization (Fan et al, 2003).…”
Section: Source Of Ore-forming Fluids and Metallogenic Modelmentioning
confidence: 99%
“…This high Hg content is reported for the first time in the gold district. The Au-Ag-Hg compound has been reported in the hypogene environment [72]. Orogenic gold with high Hg content have also been reported by [61,62].…”
Section: Impact Of Anthropogenic Activitiesmentioning
confidence: 85%
“…In the Cameroon goldfields, such high Cu content is reported for the first time. Systematic changes in alloy composition in gold detrital particles within a single hydrothermal system point to the evolution of the hydrothermal fluids in space and time [72]. It is possible that the lode source had multiple mineralizing events that produced a range of native gold generations.…”
Section: Gold Microchemical Signature and Grain Transportationmentioning
confidence: 99%
“…The formation of the Mesozoic gold deposits of the NNCC was interpreted as related to either magmatic-hydrothermal (N'dri et al, 2021;Yang et al, 2021) or metamorphic-fluid models (Goldfarb & Pitcairn, 2022;Goldfarb et al, 2001Goldfarb et al, , 2019Tomkins, 2010), which would suggest that Hg was sourced from the Mesozoic granites or the Precambrian metamorphic basement, respectively. As shown in Figure 3b, bulk ore and pyrite samples show ∆ 199 Hg values of −0.28‰ to 0.34‰, which cover a larger range than that of the Mesozoic granites (−0.21‰ to 0.13‰) and the Precambrian basement rocks (−0.37‰ to 0.11‰), suggesting that the gold deposits studied cannot be explained exclusively by any of the above-mentioned models.…”
Section: Dual Hg Sources For the Nncc Gold Depositsmentioning
confidence: 99%
“…The coeval gold deposits contain a total resource of >1,000 tonnes Au; however, their genesis remains unclear. Some studies have suggested that the ore‐forming metals are of magmatic‐hydrothermal origin (e.g., N'dri et al., 2021; Yang et al., 2021), while others classify these deposits as orogenic gold deposits in which the ore‐forming metals could be sourced from the Precambrian metamorphic basement or sediments on the top of the subducting slab (Goldfarb & Pitcairn, 2022; Goldfarb et al., 2001, 2019; Tomkins, 2010). According to Goldschmidt's geochemical classification of elements, Hg and Au belong to chalcophile elements and share similar geochemical behavior during hydrothermal processes.…”
Section: Introductionmentioning
confidence: 99%